Security vs. civil liberties: How citizens cope with threat, restriction, and ideology - Jäger, Felix (Frontiers in Political Science, 2023)
How do citizens balance their preferences for civil liberties and security in the context of political polarization? Using the case of terrorism and counter-terrorism, I argue that the willingness to support restrictions of civil liberties does not only depend on external shocks and becoming targeted by a counter-policy. Instead, citizens’ preference also depends on their ideological match with policy makers and terrorist actors. Using an original survey experiment conducted in Germany in 2022, I show how the four factors (feeling threatened by a terrorist attack, becoming targeted by a surveillance measure, ideology behind an attack and ideology of counteracting politicians) influence the attitudes of citizens and whether these factors are conditional on each other. While earlier research has focused on one kind of terrorism (mostly Islamic) this paper examines various forms of terrorism (religious, right-wing and climate extremist) and how they affect peoples’ attitudes towards civil liberties and surveillance. Results show that terrorist ideology plays a minor role, but citizens care whether they sympathize with the policy proposing party. The study extends our understanding of the political consequences of polarization, the threat perceptions of terrorism, and public support for surveillance policy.